Optimalisasi Potensi Lokal Masyarakat Rungkut Menanggal Surabaya melalui Penguatan Aset Sosial dan Material Berbasis Pengelolaan Bank Sampah - Moch Iqbal Pramudita; Agus Afandi (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2025)
Waste management remains one of the major challenges in urban areas, including Rungkut Menanggal Subdistrict, Surabaya. Although two active waste banks already exist, community participation and the optimization of social and material assets remain limited. This community empowerment program aims to optimize local potential through the strengthening of social and material assets based on waste bank activities using the Asset-Based Community Development (ABCD) approach. This approach emphasizes the utilization of existing community strengths and resources to create sustainable social transformation. The program was carried out through five participatory stages: discover, dream, design, define, and destiny. The results show a significant improvement in the community’s capacity for household waste management. Residents were able to process approximately 100 kg of organic waste into compost and create creative products such as decorative bags made from plastic waste. Moreover, collaboration among local institutions such as Karang Taruna Arkidli, PKK, Posga Venus, Posga Bumi, and KSH increased, strengthening collective action in environmental management. This program demonstrates that the ABCD approach effectively enhances social capital, increases community participation, and generates both economic and environmental benefits. Waste bank management based on local asset empowerment can serve as a model for inclusive and adaptive community development in urban environmental contexts.